Early clinical trials in chronic lymphocytic leukaemia in the UK. (15th November 2020) - Catovsky, Daniel; Else, Monica
Summary: This is an historical account of the randomised trials in chronic lymphocytic leukaemia in the UK between the years 1978 to 2004, describing their gestation, the treatments used and the main lessons learnt. Those lessons include: (1) how best to use chlorambucil, which was the first effective treatment for CLL; (2) the significant difference in survival between the sexes; and (3) the value of prognostic markers, both morphological and molecular, which continue to be relevant to current practice.